The Large Chamber Test for Toxic Fumes Analysis of Permissible Explosives - Lon D. Santis; James H. III Rowland; Dennis J. Viscusi; Mark H. Weslowski (International Society of Explosives Engineers, 1995)
This paper describes the procedure for analysis of toxic fumes from the detonation of high explosives using the Large Chamber at the U.S. Bureau of Mines (USBM), Pittsburgh Research Center (PRC). This test is specified in 30 Code of Federal Regulations (CFR) Part 15.20 (g) as a requirement for the Mine Safety and Health Administration's (MSHA) approval of an explosive as permissible for use in underground coal mines. The Large Chamber replaced the Bichel gauge and CrawshawJones (C-J) apparatus in the 1989 revision of these regulations. To determine the safety of an explosive in terms of toxic gas production, the Large Chamber Test attempts to simulate mine conditions and miners' exposure to toxic gases from explosives.